Analysis of mercury in dental personnel hair in Amphoe Hat-Yai Changwat Songkhla by cold vapor atomic absorption spectroscopic technique - Saraporn Onthong (2006)
Thesis (M.Sc., Analytical Chemistry)--Prince of Songkla University, 2006